A Brief History of Two Common Surgical Drains. Issue 1 (January 2016) - Meyerson, Joseph M.
Abstract : Abstract: The use of surgical drains is commonplace in all types of surgical procedures, and rarely do we take the time to contemplate or investigate the origins of these critical devices. Every surgeon should be familiar with the Jackson-Pratt drain and Blake drain, 2 of the most frequently used closed suction, negative-pressure drainage devices in surgery. These drains are used throughout the body in a wide variety of surgical procedures. The development and differences between these 2 devices are seldom known by the practicing surgeon. In this article, we delve into the ancient history of drains, the creation and alterations of the closed suction, negative-pressure drain that paved the way for the Jackson-Pratt and Blake drain. Finally, we will discuss the variety of reservoirs that attach to these drains and the origin of the well-known adage of when to pull a drain.